REPRESENTASI EKLEKTISISME PADA KURIKULUMSEKOLAH MENENGAH KEJURUAN (SMK) Abstract BERBASIS KOMPETENSI - Pardjono Pardjono (Jurnal Cakrawala Pendidikan, 2004)
Vocational education is facing with the problems to provide skilled workers who are able to adapt changes and have a highly moral standard. Indonesian requires high professional workers and the workers who are able to adapt the world with highly technological change and a tightly cOlT)petition within a local, national, or international. . The competency baSed and life skills oriented vocational high school curriculum, in educating workers and experts in their own voca~ion who have thinking skills, social senses, and high standard moral, it needs an eclectic foundation. Idealism, realism, and reconstructionism school ofthoughts that are employed eclectically may provide base for the vocational education curriculum. Key words: curriculum, vocational education, philosophy.